RELASI ANTARA MORALITAS DAN HUKUM: PERSPEKTIF FILSAFAT HUKUM KONTEMPORER - Junaedi, Oding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The relationship between morality and law is a fundamental debate in legal philosophy that continues to develop today. This study aims to analyze the relationship between law and morality from the perspective of contemporary legal philosophy and explore the influence of morality in the formation, interpretation, and application of law in the modern legal system. The method used in this study is a qualitative approach with a literature study of various legal theories, including legal positivism, natural law theory, and critical thinking in legal philosophy. The results of the study show that although law and morality have different characteristics, the two cannot be completely separated. In contemporary legal philosophy, thoughts such as those put forward by Ronald Dworkin emphasize that law does not only consist of formal rules, but also contains moral principles that function in the process of interpreting law. In addition, morality plays a significant role in the formation of law, especially in regulations relating to human rights and social justice. In the application of law, morality is also an important consideration for law enforcement officers in the use of legal discretion to achieve substantive justice. The conclusion of this study emphasizes that law cannot stand autonomously without considering the moral values ​​that develop in society. Therefore, a stronger integration of morality in the legislative process and law enforcement is needed to create a more just law. In addition, the development of interdisciplinary studies between law and morality is needed to enrich the understanding of the role of morality in the modern legal system.